Optoelectronic properties of atomically thin ReSSe with weak interlayer coupling. Issue 11 (1st March 2016) - Liu, Fucai; Zheng, Shoujun; Chaturvedi, Apoorva; Zólyomi, Viktor; Zhou, Jiadong; Fu, Qundong; Zhu, Chao; Yu, Peng; Zeng, Qingsheng; Drummond, Neil D.; Fan, Hong Jin; Kloc, Christian; et al.
Abstract : Rhenium dichalcogenides alloy of ReSSe shows a high mobility of 3 cm 2 V −1 s −1 and a photoresponsivity of 8 AW −1, together with the in-plane anisotropy and tunable bandgap. It provides new systems for the study of 2D materials with in-plane anisotropy. Abstract : Rhenium dichalcogenides, such as ReS2 and ReSe2, have attracted a lot of interests due to the weak interlayered coupling in these materials. Studies of rhenium based dichalcogenide alloys will help us understand the differences between binary rhenium dichalcogenides. They will also extend the applications of two-dimensional (2D) materials through alloying. In this work, we studied the optoelectronic properties of ReSSe with a S and Se ratio of 1 : 1. The band gap of the ReSSe alloy is investigated by optical absorption spectra as well as theoretical calculations. The alloy shows weak interlayered coupling, as evidenced by the Raman spectrum. A field-effect transistor based on ReSSe shows typical n-type behavior with a mobility of about 3 cm 2 V −1 s −1 and an on/off ratio of 10 5, together with the in-plane anisotropic conductivity. The device also shows good photoresponse properties, with a photoresponsivity of 8 A W −1 . The results demonstrated here will provide new avenues for the study of 2D materials with weak interlayer interactions and in-plane anisotropy.